Magnetic clustering of Ni2+ ions in metal-ceramic nanocomposites obtained from Ni-exchanged zeolite precursors. Issue 14 (1st October 2018) - Barrera, G.; Tiberto, P.; Esposito, S.; Marocco, A.; Bonelli, B.; Pansini, M.; Manzoli, M.; Allia, P.
Abstract: Metal-ceramic nanocomposites containing nominal 15% wt. Ni were produced by a smart, scalable process involving a suitable thermal treatment of Ni-exchanged zeolite precursors, and were investigated by dc magnetic techniques between 2 and 300 K. Two main magnetic phases were detected in all studied materials: globular magnetic nanoparticles with average diameters in the 10–20 nm range, and Ni 2+ ions embedded in the host ceramic matrix. The blocking temperature of Ni 0 nanoparticles is well above room temperature. The magnetic signal from nanoparticles dominates at high temperature; however, a clear paramagnetic signal from Ni 2+ ions emerges when the temperature is decreased. The magnetic moment per Ni ion is in agreement with typical values found in Ni-containing zeolites. Magnetic susceptibility and FC/ZFC curves point to the existence of a weak interaction among Ni 2+ ions (Néel temperature TN < 15 K) which results in the formation of ferrimagnetic-like clusters below about 30 K. In each cluster, the individual magnetic moments respond in a collective way with blocking temperatures less than 5 K.